The Effectiveness Analysis of the Implementation of Class Active Learning on Students Character in Two Ways Learning Process - Susiloningsih, Esti; Tahir, Abdul; Setiono, Agus; Vanda, Yoiceta; Sudadi (Mudir : Jurnal Manajemen Pendidikan, 2023)
It is clear from the practical data on the ground that students still struggle to comprehend the materials. This may be brought on by pupils who are less engaged in the learning process or even the teacher's boring teaching style, which makes students disinterested. The purpose of this study is to ascertain the contribution of learning to the development of student character. This study's methodology combines a qualitative approach with a descriptive analytic technique. In this study, there are two different types of data sources primary data and secondary data. Direct interviews with the principal, deputy principal, deputy curriculum and instructors, students, and the outcomes of observations served as the primary data sources. In contrast, secondary data sources are gathered from the examination of records, manuscripts, and archives pertaining to the use of Active Learning in learning and its effects on enhancing students' character. According to the findings of the researcher's study, religious activities both inside and outside of the classroom are used to contain the components of the application of Active Learning in learning. According to the study's findings, students' religious, moral, and performance character are successfully shaped through the use of active learning techniques in learning.